Using solar energy to reduce heat stress in hot and humid offices-an alternative to conventional airconditioning. - Santos, Arturo Martin B. (Philippine Engineering Journal)
Among heat acclimatized people, sweating is often quite efficient. Supplying dried only air to the immediate vicinity of office workers in hot and humid regions may be a promising low cost alternative to traditional air conditioning. 123 heat adapted subjects participated in six one hour exposures in cubicles in a warm room without air conditioning. Each subject had individually adjustable air outlets both above and below the desk. The temperature and humidity of the supply air was varied in a blinded and randomized design. One exposure had no air supply. At the end of each exposure the perceptions of subjects, water intake, skin temperatures, sweating and a simple performance measure were registered. The supply of dehumidified but not cooled air significantly increased acceptability and reduced most of the monitored indicators of heat stress. Solar energy was used in the air drying process and this may reduce the electricity consumption for drying considerably.